perception of Romance Relationship Standards of Generation Z on TikTok - Lessy, Putri Ballgis; Dimyati, Dindin (eProceedings of Management, 2025)
This research investigates how Generation Z perceives romantic relationship standards on TikTok, focusing on howcurated content influences their expectations and emotional responses. TikTok introduces idealised romanticrepresentations that shape how young people interpret love and relationships. This study applies Richard Gregory’sConstructivist Theory of Perception to examine how prior experiences, incomplete information, and digital cuesinfluence users’ perception of relationship reality. A qualitative phenomenological method was used, involving seveninformants aged 18–24 from Jakarta and Bandung. Data were collected through in-depth interviews and analysedusing Jhonny Saldaña thematic analysis to identify patterns in how romantic content on TikTok shapes and reinforcesromantic ideals. The findings show that informants often internalised unrealistic standards, resulting in insecurity,disappointment, and relational pressure. However, some developed awareness of the curated nature of suchportrayals. Further studies may explore emotional well-being impacts, screen time, gender differences, and culturalcontexts using quantitative methods to deepen understanding.Keywords: Generation Z, TikTok, Romantic Relationship, Expectations